GENETIC CONTROL OF ULTRA-EARLINESS IN CHINESE BARLEY LANDRACES - I. A. Zveinek; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции)
Ultra-early maturity of the Chinese barley landraces k-15881 (Hordeum vulgare L. var. coeleste L.) and k-15882 (var. nudipyramidatum Koern.) from VIR’s barley collection is controlled by three identical recessive genes. This homozygous genotype determines the period from shoot emergence to heading =32 days, with two recessives genes =36 days, and with one =40 days. One dominant allele of the gene contributes approximately 4 days to the earliness. New breeding source material with different times of heading to develop adaptable cultivars may be obtained by crossing these forms with later maturing commercial cultivars.